2009
DOI: 10.14221/ajte.2009v34n3.4
|View full text |Cite
|
Sign up to set email alerts
|

Social Justice, Pedagogy and Multiliteracies: Developing Communities of Practice for Teacher Education

Abstract: (Wenger, 1998;Wenger et al., 2002

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…This study found that CALD pre-service teachers who experienced diversity and difference as obstructive to shared understanding and interaction failed to become members of a community of practice or achieved minimal membership. Participants of learning and teaching communities often did not operate on the central tenets of a community of practice: that is, through joint enterprise, mutuality and inclusion of novices (Wenger, McDermott & Snyder, 2002; see also Cumming-Potvin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…This study found that CALD pre-service teachers who experienced diversity and difference as obstructive to shared understanding and interaction failed to become members of a community of practice or achieved minimal membership. Participants of learning and teaching communities often did not operate on the central tenets of a community of practice: that is, through joint enterprise, mutuality and inclusion of novices (Wenger, McDermott & Snyder, 2002; see also Cumming-Potvin, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…The English classroom is an environment well-suited to prepare young people to engage as future citizens of a complex, challenging and constantly evolving community by 'truly engaging with difference' (Rennie, 2009, p. 13). Influenced by a 'multiliteracies' approach that acknowledges the need to prepare young people as informed citizens able to participate fully in an increasingly diverse and complex society (Anstey, 2002;New London Group, 2000), English teaching has clear potential to bring social justice into the classroom (Cumming-Potvin, 2009;Exley, Woods, Lunn, Walker & Whiteford, 2014). A multiliteracies approach that incorporates 'situated practice', with its emphasis on working with the kinds of texts the students use themselves (Cope and Kalantzis, 2015, p. 4), also has the potential to help every student feel they belong in the learning community and are connected to the content presented.…”
Section: Towards Curricular Justice -What Can Teachers Do?mentioning
confidence: 99%
“…As learners engage with contemporary literacy landscapes, the concept of multiliteracies suggests that human knowledge is constructed across social, cultural and material communities through existing and emerging practices (Cumming-Potvin, 2009;Mills, 2011). A multiliteracies framework (The New London Group, 2000) views literacy as more than technical skills but also as highly complex social, cultural and historical processes.…”
Section: Theoretical Considerations: Multiliteracies and Communities mentioning
confidence: 99%